Laparoscopic cholecystectomy: Assessing the operation outcomes of a single surgeon in his first two years - Ibrahim Halil Ocal; Mustafa Ocal; Atilla Genc; Atilla Badem (Medicine Science)
Laparoscopic cholecystectomy (LC) has solidified its role as the gold standard for managing symptomatic gallstones, acclaimed for its short hospital stay, quick recovery, minimal trauma, and less need for postoperative pain management. This study aims to address potential trust issues related to LC procedures and the surgeon by evaluating the overall conditions and outcomes of patients who underwent laparoscopic cholecystectomy at a single center by a single doctor within two years following the completion of their specialty training. The goal is to assess and establish the reliability of LC applications and the surgeon's competency in a practical setting. This retrospective study analyzed hospital records from 2021 to 2023, involving patients who underwent laparoscopic cholecystectomy performed by a single surgeon who completed his specialty training two years prior. The study comprehensively evaluated the medical files of 253 patients treated by this surgeon. Key findings reveal an average surgery time of 37.9 minutes-significantly less than commonly cited durations in medical literature. The study also reported a notably low conversion rate to open surgery at 2.4%, which underscores the safety and feasibility of LC even in complicated cases like acute cholecystitis. While complications were minimal, the occurrence of bile duct injuries at a rate of 3.1% suggests the need for improved training and preventive protocols. This research emphasizes the critical role of continual training and experience for young surgeons, aiming to bolster public confidence in their capabilities and promoting wider acceptance of minimally invasive surgical techniques. [Med-Science 2025; 14(1.000): 43-8]